Do weaver ants affect arthropod diversity and the natural‐enemy‐to‐pest ratio in horticultural systems?. (19th April 2013) - Peng, R.; Christian, K.
Abstract: High biodiversity is an important component of sustainable agricultural systems, and previous studies have found that increases in the diversity of the natural enemies of pests are associated with decreases in pest populations. Weaver ants are well known for their highly territorial and aggressive behaviour and for their control efficiency of many insect pests in tropical crop trees. Because of this, the ants have been used as a key component in integrated pest management (IPM) programmes for tropical crop trees. In implementing the IPM programmes, we received a number of enquiries related to whether weaver ants have negative effects on arthropod diversity and other natural enemies in orchard systems due to their aggressive behaviour. To answer these questions, we regularly sampled canopy arthropods in cashew and mango orchards in the Northern Territory of Australia in 1996, 2002 and 2003. We sampled, using a vacuum sampler, orchards with and without weaver ants. Cashew and mango plots with abundant weaver ants had similar or higher canopy arthropod and natural enemy diversity and similar ratios of natural enemies to insect pests, compared with plot where the weaver ant was absent. The study also showed that the application of insecticides reduced arthropod diversity and the ratio of natural enemies to insect pests in a mango orchard. However, insecticide spray did not affect natural enemy diversity and abundance, which may be related to a high immigration rate of natural enemies in small plots surrounded by areas that were not sprayed.